CISG and the unification of international trade law / Bruno Zeller - Zeller, Bruno (Routledge-Cavendish, 2007)
Pushing the boundaries between domestic and unified laws, this book explores the differences between unification and harmonization. It provides a critical examination of the Convention for the International Sale of Goods (CISG), the advances of international jurisprudence and the role of domestic courts.